2020
DOI: 10.1038/s41593-020-00761-w
|View full text |Cite
|
Sign up to set email alerts
|

Vector trace cells in the subiculum of the hippocampal formation

Abstract: Successfully navigating in physical or semantic space requires a neural representation of allocentric (map-based) vectors to boundaries, objects, and goals. Cognitive processes such as path-planning and imagination entail recall of vector representations, but evidence of neuron-level memory for allocentric vectors has been lacking. Here we describe a novel neuron type (Vector Trace cell, VTC) whose firing generates a new vector field when a cue is encountered, and also a ‘trace’ version of that field for hours… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 71 publications
5
58
1
Order By: Relevance
“…These 2 classes of cells are modulated differently by sharp-wave ripples of the CA1 and have different intrinsic connectivity [38]. Furthermore, a series of recent in vivo studies identified subpopulations in the subiculum with different spatial firing characteristics [29,[53][54][55].…”
Section: Functional Subclasses Of Neurons In the Subiculum May Play Key Roles In Hippocampal-dependent Action In A Visual Contextual Memomentioning
confidence: 99%
“…These 2 classes of cells are modulated differently by sharp-wave ripples of the CA1 and have different intrinsic connectivity [38]. Furthermore, a series of recent in vivo studies identified subpopulations in the subiculum with different spatial firing characteristics [29,[53][54][55].…”
Section: Functional Subclasses Of Neurons In the Subiculum May Play Key Roles In Hippocampal-dependent Action In A Visual Contextual Memomentioning
confidence: 99%
“…Landmark-based navigation, extensively documented in humans 22,23,25,29 and animals 44 , may lead to asymmetric paths that depend on the distribution of views in the environment. Furthermore, many animals, such as rodents 45 , bats 46,47 and cats 48 , rely on direction 42,43,45,49,50 for vector navigation 50,51 . Human subjects in laboratory studies likewise rely on direction for navigation, taking a route to the first destination that begins in the direction of subsequent destinations 52 , and rely on neural representations of both Euclidian distance and direction to destination 42 .…”
Section: Stochastic Distance Minimizationmentioning
confidence: 99%
“…For example, retrosplenial neurons code the egocentric turning direction at different points along a linear track, with responses that also depend upon broader scale coordinates such as position along the route or allocentric spatial location within a larger room ( Alexander and Nitz, 2015 , 2017 ) and has been shown to be necessary for using visual distal cues to solve spatial tasks( Hindley et al., 2014 ). More recently, neurons in retrosplenial cortex have been shown to respond to the egocentric position of barriers ( Alexander et al., 2020 ; van Wijngaarden et al., 2020 ) similar to egocentric coding of barriers in postrhinal cortex, lateral entorhinal cortex, and dorsal striatum ( Gofman et al., 2019 ; Hinman et al., 2019 ; LaChance et al., 2019 ; Wang et al., 2018 ) and allocentric coding of barriers in entorhinal cortex ( Solstad et al., 2008 ) and subiculum ( Lever et al., 2010 ; Poulter et al., 2021 ). Some neurons in the retrosplenial cortex have been shown to exhibit broad responses to changes in environmental context such as a change in color of barriers, auditory cues, and odors ( Miller et al., 2021 ), as well as responses to goal locations ( Miller et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%